External evaluation of French as a foreign language: the DELF-DALF diplomas within multilingual contexts - Moracho-Baquedano, Iosu (My University, 2018)
The relevance of foreign languages within educational systems is indisputable. They have become a key element on account of globalisation, new technologies and the arrival of the so-called Communication Era. Governments and educational centres, motivated by the pressure of the labour market and the very interest of educational agents (teachers, families, students), have been crucial to make of this field a prominent axis of educational projects. In an increasingly global and competitive society, the external evaluation of languages has been established to validate the quality of educational systems and to provide students with certificates and diplomas which grant access to different educational institutions, international mobility or the labour market itself. In particular, this Master’s Dissertation analyses the DELF-DALF diplomas (Diplôme d’Études de Langue Française and Diplôme Approfondi de Langue Française). These certifications are organised by the French Ministry of Education through the CIEP (Centre International d’Études Pédagogiques) and have been adapted to the Common European Framework of Reference for Languages (CEFRL). The interest of this work is to analyse how language proficiency is evaluated and certified by external institutions within multilingual environments. We thoroughly examine the evaluation method of these diplomas regarding their evaluation rubrics, descriptors and format so as to extract some of the specific circumstances that may influence the linguistic performance of bilingual speakers. The author, teacher of French as a foreign language and corrector-examiner of DELF-DALF diplomas, performs a theoretical analysis according to the foundations of the exams, the linguistic features of bilingual speakers and the public-domain correction criteria of the DELF-DALF diplomas.
Keywords: bilingual education; CEFRL; DELF-DALF; external evaluation; French as a Foreign Language (FFL - FLE); educación bilingüe; Máster Universitario en Educación Bilingüe